A case of juvenile CLN1– challenge in diagnosis and epilepsy treatment. Issue 2 (4th March 2021) - Kravljanac, Ruzica; Sims, Katherine
ABSTRACT: Introduction Classic onset of CLN1 disease is within the first year of life with developmental arrest, epilepsy and rapid progression. In an atypical variant of CLN1 disease onset is later in the juvenile epoch. Although epilepsy in the juvenile form of CLN1 often is less severe than in typical CLN1, treatment of seizures and status epilepticus may be challenging. Case presentation The clinical course, misdiagnosis and epilepsy phenotype are presented in a girl with juvenile CLN1. Cognitive and neurologic regression started at age 5.5 years. Epilepsy was a major clinical issue as the patient suffered from focal seizures, recurrent status epilepticus and epilepsia partialis continua. In one episode of refractory status epilepticus, the patient had significant bradycardia associated with the intravenous infusion of levetiracetam. Diagnosis was made at the age of 12 years, based on palmitoyl protein-thioesterase (PPT) enzyme deficiency and genetic testing that documented a homozygous exon missense mutation in the CLN1 gene (PPT1, c.541G>A, p.Val181Met). Discussion Epilepsy in all NCL patients is a major clinical issue and presumed related to neuronal excitation and epileptogenesis. The treatment of status epilepticus, in juvenile CLN1 patients, presents a particular challenge and requires monitoring of potential serious pharmacologic side effects of therapy.